The intergenerational transmission of gender role attitudes and its implications for female labor force participation - Lídia Farré; Francis Vella (Institute for the Study of Labor (IZA), 2007)
Using a sample of mother-child pairs from the National Longitudinal Survey of Youth 1979 (NLSY79) and the Young Adults of the NLSY79 we explore the relationship between a woman's attitudes towards the role of females in the labor market and the attitudes of her children. We also examine whether this intergenerational cultural link has implications for the labor market behavior of the females in the NLSY79. We find that a woman's attitudes have a statistically significant effect on her children's views towards working women. Furthermore we find that this cultural transmission influences female labor market decisions. Our results imply that a woman's view regarding the role of females in the labor market and family not only affects the labor market force participation decision of her daughter, but also has an equally strong association with the labor force participation of the wife of her son. These results indicate that the transmission of gender role attitudes contributes to the persistence of economic status across generations.
urn:nbn:de:101:1-20080401283
Keywords: 330; Frauenerwerbstätigkeit; Geschlecht; Soziale Werte; Generationenbeziehungen; USA